2021
DOI: 10.1021/acs.jafc.0c05950
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Nonpersistent Pesticides in Small Volumes of Human Breast Milk with Ultrahigh Performance Liquid Chromatography Coupled to Tandem Mass Spectrometry

Abstract: Existing methods for the analysis of pesticides in human breast milk involve multiple extraction steps requiring large sample and solvent volumes, which can be a major obstacle in large epidemiologic studies. Here, we developed a simple, low-volume method for extracting organophosphates, pyrethroids, carbamates, atrazine, and imidacloprid from 100 to 200 μL of human breast milk. Multiple extraction protocols were tested including microwave-assisted acid/base digestion and double-solvent extraction with 2 or 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…According to the WHO classification [ 10 ], the prevalence of anemia among pregnant women in China (30.7%) found during this research would be classified as a “moderate” public health problem (20.0–39.9%). This was higher than the 13.6% stated in the “Report on nutrition and chronic diseases of Chinese residents (2020)” published by the China Nutrition and Health Surveillance (CNHS) [ 72 ].…”
Section: Discussionmentioning
confidence: 70%
“…According to the WHO classification [ 10 ], the prevalence of anemia among pregnant women in China (30.7%) found during this research would be classified as a “moderate” public health problem (20.0–39.9%). This was higher than the 13.6% stated in the “Report on nutrition and chronic diseases of Chinese residents (2020)” published by the China Nutrition and Health Surveillance (CNHS) [ 72 ].…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies also showed that a major removal pathway might be 3-PBA biodegradation by soil microorganisms . In addition, the banning of persistent-halogenated pesticides in the 1970s and 1980s massively increased the use of pyrethroids in agricultural farms and in and around homes. , Long-term exposure to non-persistent pesticides is associated with multiple health problems, including neurological defects, cancer, and infertility. Therefore, the occurrence of pyrethroids in the soil environment is a major concern.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the short 3-PBA half-life may be caused by volatilization under high temperatures and degradation losses. Additionally, the pK a value of 3-PBA (3.95) indicates that 3-PBA easily reacts in an alkaline environment. Other studies have shown that 3-PBA degradation increases with the increase in soil pH. , The application of diammonium phosphate and urea fertilizer to C2 field on June 12th potentially caused an alkaline soil environment, a probable reason for the short 3-PBA half-life in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on MAE applied to milk and cheeses were carried out for the extraction and determination of aflatoxins and pesticides [28,29], biogenic amines [30], bioactive peptides [31], and organic acids [32]. Moreover, Dvoršćak et al described for the first time the use of MAE for organic pollutants from human milk samples, highlighting the influence of sample preparation and pretreatment [33].…”
Section: Introductionmentioning
confidence: 99%